Low-dose methotrexate adverse reaction risk in renal impairment: pharmacovigilance and physiological pharmacokinetic model assessment - Zhang, Lichang; Li, Jianling; Wang, Xin; Zhang, Yaolei; Gao, Sen; Dong, Deshi; Zhu, Yanna; Yang, Shilei (Frontiers in Pharmacology, 2025)
ObjectiveLow-dose methotrexate (LD-MTX), a treatment regimen involving weekly doses ≤20 mg, is widely used in rheumatoid arthritis. Methotrexate (MTX) is primarily excreted via the kidneys. However, the assessment protocol for the adverse reaction risk threshold of the LD-MTX dosing regimen in renal impairment remains inadequate. This study aims to use pharmacovigilance analysis and physiologically-based pharmacokinetic (PBPK) model to combine the analysis of the risk of adverse reactions of LD-MTX in patients with renal impairment.MethodsCollected and analyzed disproportionate signals from adverse reaction reports on MTX in patients with renal impairment from the FDA Adverse Event Reporting System (FAERS) from Q1 2004 to Q3 2024. The restricted cubic spline (RCS) model explored the nonlinear relationship between MTX maximum plasma concentration and dose to derive risk thresholds. The PBPK model was developed and validated using MTX data in healthy adults, and further extended to chronic kidney disease (CKD) populations to simulate dose risks.ResultsFAERS analysis revealed heightened risks of hematological disorders, hepatic impairment, and pulmonary adverse events (AEs) with MTX in renal impairment. The optimized threshold based on RCS and the PBPK model simulation results indicated that the risk of adverse reactions increased starting from CKD stage 2.ConclusionLD-MTX confers increased adverse reaction risks in renal impairment, notably from CKD stage 2 or higher, necessitating dose adjustments and vigilant monitoring.